Dynamic assessment of multi-organ level dysfunction in patients recovering from COVID-19 - Gupta, Ayushman (2024)
Since its emergence, the impact of acute coronavirus disease (COVID-19) on mortality has been profound. However, in June 2020 there was an emerging picture of prolonged recovery of people who had survived the acute infection. A huge proportion of individuals experienced persisting and debilitating symptoms, such as fatigue, after resolution of the acute infection, with many affected previously devoid of pre-existing medical conditions and disability. This has resulted in increased time off from or return to work. In an era where the initial project for this PhD was put on hold due to recruitment of patients that were vulnerable to severe infection (assessment of cerebrovascular and cardiovascular haemodynamic response to exercise in patients with COPD), the focus turned to addressing the long term impacts of COVID-19. Whilst 3 years on there is now an abundant literature on symptoms, the mechanisms remain poorly understood. In this thesis, a detailed physiological and metabolic phenotyping was conducted of patients who survived severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) related hospitalisation and healthy control volunteers, focussing on muscle, metabolic, cardiovascular and cerebrovascular properties to elicit mechanisms that drive symptoms +/- organ impairment.